TRICHOME AND ARTEMISININ REGULATOR 2 positively regulates trichome development and artemisinin biosynthesis in Artemisia annua - Zhou, Zheng (The New phytologist, 2020)
© 2020 The Authors. New Phytologist © 2020 New Phytologist Trust.